Characterisation of the Metabolism of Pogostone In Vitro and In Vivo Using Liquid Chromatography with Mass Spectrometry. Issue 2 (26th November 2013) - Li, Yucui; Su, Ziren; Lin, Shuhai; Li, Chuwen; Zhao, Ya; Gao, Xiang; Lai, Yongquan; Wu, Xiaoli; Wu, Hanzhi; Cai, Zongwei; Lai, Xiaoping
ABSTRACT Introduction Pogostone possesses potent anti‐bacterial and anti‐fungal activities and has been used for the quality control of essential oil of Pogostemon cablin. Pogostone is easily absorbed after oral administration but its metabolism in mammals remains elusive. Objective To investigate the metabolic profile of pogostone in vitro and in vivo. Methods High‐performance liquid chromatography coupled with mass spectrometry (LC–MS) techniques were employed. Orbitrap MS and ion trap tandem mass spectrometry (MS/MS) were utilised to analyse the metabolism of pogostone by virtue of the high sensitivity and high selectivity in the measurement. In vitro experiment was carried out using rat liver microsomes while the in vivo study was conducted on rats, which were orally administered with pogostone (80 mg/kg). Results In total, three mono‐hydroxylated, one di‐hydroxylated, one mono‐oxygenated, one di‐oxygenated metabolite, one hydrolysis and one hydroxy conjugated metabolites were found. In addition hydroxylation was demonstrated to be a major metabolic pathway of pogostone. Conclusion LC–MS was demonstrated to be a powerful tool for the metabolite identification of pogostone. The tentative identification of metabolites provides an insight for the metabolic clues of pogostone. Copyright © 2013 John Wiley & Sons, Ltd.